2016
DOI: 10.1007/s12253-016-0084-3
|View full text |Cite
|
Sign up to set email alerts
|

Region Specific Differences of Claudin-5 Expression in Pediatric Intracranial Ependymomas: Potential Prognostic Role in Supratentorial Cases

Abstract: Ependymomas are common pediatric brain tumors that originate from the ependyma and characterized by poor prognosis due to frequent recurrence. However, the current WHO grading system fails to accurately predict outcome. In a retrospective study, we analyzed 54 intracranial pediatric ependymomas and found a significantly higher overall survival in supratentorial cases when compared to infratentorial tumors. Next we performed region-specific immunohistochemical analysis of the ependyma in neonatal and adult epen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…Claudin-5, the prototypical BBB claudin, distributes at the junctions in large penetrating stromal vessels in rat and mouse and possibly in some smaller vessels [74,82,146]. Its expression in the choroidal epithelium was not detected in rat and mouse, but was recently described in human neonates [164]. Claudin-11 was immunodetected at epithelial junctions in mouse choroid plexus [166].…”
Section: Paracellular Barrier Properties Of the Choroid Plexus Epithementioning
confidence: 99%
“…Claudin-5, the prototypical BBB claudin, distributes at the junctions in large penetrating stromal vessels in rat and mouse and possibly in some smaller vessels [74,82,146]. Its expression in the choroidal epithelium was not detected in rat and mouse, but was recently described in human neonates [164]. Claudin-11 was immunodetected at epithelial junctions in mouse choroid plexus [166].…”
Section: Paracellular Barrier Properties Of the Choroid Plexus Epithementioning
confidence: 99%
“…Claudin‐5 is a protein of tight junction membranes reported to be expressed by endothelial cells of the brain and ependymoma tumor cells . Immunohistochemical analysis showed that claudin‐5 (Abcam plc, Cambridge, UK) was expressed in the endothelial cells of all three subependymomas and in an ependymoma.…”
Section: Case Reportsmentioning
confidence: 99%
“…Microcysts containing mucoid material were frequently observed ( Figure 3A Claudin-5 is a protein of tight junction membranes reported to be expressed by endothelial cells of the brain and ependymoma tumor cells. 8,9 Immunohistochemical analysis showed that claudin-5 (Abcam plc, Cambridge, UK) was expressed in the endothelial cells of all three subependymomas and in an ependymoma. The subependymomas and the ependymoma sample showed focal intracytoplasmic dot-like and cytoplasmic membrane expression of claudin-5 ( Figure 3C,D), with the ependymoma sample also showing linearly strong positive staining for claudin-5 at the lumina of the ependymal rosettes ( Figure 3D).…”
Section: Cytological and Histopathological Findingsmentioning
confidence: 99%